Comparison of 4D Flow MRI to 2D Flow MRI in the pulmonary arteries in healthy volunteers and patients with pulmonary hypertension - Sieren, Malte Maria; Berlin, Clara; Oechtering, Thekla Helene; Hunold, Peter; Drömann, Daniel; Barkhausen, Jörg; Frydrychowicz, Alex (PloS one, 2019)
4D and 2D phase-contrast MRI (2D Flow MRI, 4D Flow MRI, respectively) are increasingly being used to noninvasively assess pulmonary hypertension (PH). The goals of this study were i) to evaluate whether established quantitative parameters in 2D Flow MRI associated with pulmonary hypertension can be assessed using 4D Flow MRI; ii) to compare results from 4D Flow MRI on a digital broadband 3T MR system with data from clinically established MRI-techniques as well as conservation of mass analysis and phantom correction and iii) to elaborate on the added value of secondary flow patterns in detecting PH. 11 patients with PH (4f, 63 ± 16y), 15 age-matched healthy volunteers (9f, 56 ± 11y), and 20 young healthy volunteers (13f, 23 ± 2y) were scanned on a 3T MR scanner (Philips Ingenia). Subjects were examined with a 4D Flow, a 2D Flow and a bSSFP sequence. For extrinsic comparison, quantitative parameters measured with 4D Flow MRI were compared to i) a static phantom, ii) 2D Flow acquisitions and iii) stroke volume derived from a bSSFP sequence. For intrinsic comparison conservation of mass-analysis was employed. Dedicated software was used to extract various flow, velocity, and anatomical parameters. Visualization of blood flow was performed to detect secondary flow patterns. Overall, there was good agreement between all techniques, 4D Flow results revealed a considerable spread. Data improved after phantom correction. Both 4D and 2D Flow MRI revealed concordant results to differentiate patients from healthy individuals, especially based on values derived from anatomical parameters. The visualization of a vortex, indicating the presence of PH was achieved in 9 /11 patients and 2/35 volunteers. This study confirms that quantitative parameters used for characterizing pulmonary hypertension can be gathered using 4D Flow MRI within clinically reasonable limits of agreement. Despite its unfavorable spatial and lesser temporal resolution and a non-neglible spread of results, the identification of diseased study participants was possible.